Reconstruction of submarine eruption processes from FTIR volatile analysis of marine tephra: Example of Oomurodashi volcano, Japan - McIntosh, Iona M.; Aoki, Kaori; Yanagishima, Taiki; Kobayashi, Makoto; Murata, Masanori; Suzuki, Takehiko (Frontiers in Earth Science, 2022)
Tephra layers in marine sediments are widely used to correlate and date paleoclimate and paleoceanography records, and to determine spatiotemporal changes in magmatic evolution and eruption frequency. Dissolved matrix glass H2O contents of marine tephra could potentially inform understanding of eruption processes but are rarely used due to the issue of secondary hydration after deposition. Recent advancements in Fourier transform infrared spectroscopy (FTIR) volatile analysis have enabled reconstruction of original water contents of hydrated volcanic glasses. These new FTIR analysis methods offer a new way to investigate tephra stored in marine sedimentary archives. We present a case study of the Od-1 tephra layer in marine sedimentary core C9010E, drilled ~40 km south of the Boso peninsula in Japan. This tephra was erupted by the shallow silicic submarine Oomurodashi volcano in the northern Izu-Bonin arc at ~13.5 ka. Our FTIR volatile data show it has been affected by secondary hydration, with the extent of hydration controlled by grain size and porosity characteristics. Numerical modelling of low temperature hydration suggests FTIR data offer an additional method for estimating eruption ages of marine tephra. OH contents, unaltered by low temperature secondary hydration, record low ambient eruptive pressures for all grain sizes and tephra types i.e., blocky and dense or pumiceous. Consideration of hydrostatic pressure gradients and past sea level at Oomurodashi shows that the majority of tephra volatile data cannot be explained by quench within a submarine eruption plume. Instead, OH contents record quench fragmentation within the shallow submarine edifice. Physical characteristics of the tephra are consistent with the formation of these tephra by explosive phreatomagmatic eruption processes. Together these OH data and tephra characteristics support the interpretation that the Od-1 tephra layer was formed by the same shallow phreatomagmatic eruption that formed the existing Oomuro Hole crater and that produced subaerial tephra deposits on nearby Izu-Oshima and Toshima islands. This study demonstrates the crucial contribution that imaging FTIR analysis can make to the interpretation of degassing and eruption processes of volcanic glasses, particularly vesicular pyroclasts and/or glasses affected by secondary hydration, and will add an important new dimension to marine tephra research.